Discourse of Aestheticism/Totalitarianism (On Sociopolitical Theory of Avant-garde) - Rykov, Anatolii V. (Actual Problems of Theory and History of Art, 2014)
The paper examines the issues of the general theory of avant-garde. The author considers the examples of convergence between aestheticism and totalitarian paradigm from Baudelaire to Sherrie Levine. Special attention is paid to Seurat’s “Grande Jatte”, Franz Marc’s “100 Aphorisms”, Giuseppe Terragni’s photomontage at the Exhibition of the Fascist Revolution (“Mostra della Rivoluzione Fascista”, 1932) and Sherrie Levine’s “Crystal skull” (2010). Analyzing the problems concerning the origin of avant-garde art and totalitarian thought, the author shows the complex role of Modernist artists and theorists in the rise of totalitarianism. Focusing on the problems of Walter Benjamin’s theory of art, the author investigates the virulent features of aestheticism, its extremist and negative aspects. The paper explores the common ground between avant-garde and politics, political dimension of aesthetic thought and aestheticism as its radical form. The author draws the conclusion that aestheticism with its myths and concepts is an important part of both Modernist and totalitarian projects.